Peningkatan Mutu Pendidikan Melalui Perencanaan Mutu Strategis - Ketut Bali Sastrawan (Jurnal Penjaminan Mutu, 2019)
Education is a process of humanizing humans to be able to actualize themselves in life, where good education is education that does not only prepare students for a profession or position, but to solve the problems it faces in daily life. Improving the quality of education is directed at improving the quality of Indonesian human beings through training, thinking, sports, and sports in order to have competitiveness in facing global challenges. Increasing the relevance of education is intended to produce graduates who are in accordance with the demands of the needs of Indonesia's natural resource potential. Steps that can be taken to improve the quality of education, namely: strengthening the curriculum, strengthening the capacity of school management, strengthening educational resources, continuous improvement and fact-based management.